Bacillus thuringiensis Exopolysaccharide BPS-2 Ameliorates Ulcerative Colitis in a Murine Model Through Modulation of Gut Microbiota and Suppression of the NF-κB Cascade - Zexin Gao; Huan Li; Jungang Wen; Wenping Ding; Jie Yu; Yue Zhang; Xiaojuan Song; Jianrong Wu (Foods)
This study investigated the therapeutic potential of Bacillus thuringiensis extracellular polysaccharide BPS-2 in dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) murine models. BPS-2 demonstrated significant efficacy in ameliorating UC-associated pathologies through three principal mechanisms: (1) attenuating histopathological damage while preserving colon epithelial integrity, (2) modulating immune marker expression patterns in colon tissues, and (3) restoring gut microbiota homeostasis. BPS-2 exhibited multi-faceted protective effects on the gut by mitigating oxidative stress responses and enhancing short-chain fatty acid biosynthesis, leading to an improved gut microbial community structure. Molecular docking analysis displayed strong binding affinity (ΔG = −7.8 kcal/mol) between the BPS-2U fragment and the Nuclear Factor κB (NF-κB) p50/p65 heterodimer, suggesting the potential disruption of NF-κB signaling pathways. Complementary molecular dynamics simulations revealed exceptional conformational stability in the p65-BPS-2U complex. These findings establish BPS-2 as a natural food additive that modulates the microbiota-barrier–inflammation axis through dietary intervention, offering a novel strategy to alleviate UC.